Challenges in Embracing Green Supply Chain in Morocco's Auto Industry - Fatima Zahra Fatih; Linlin Zhang (ETIKONOMI, 2023)
As global environmental awareness grows, businesses are increasingly pressured to integrate environmentally responsible practices into their supply chains. However, the automotive industry in Morocco needs to be faster to embrace Green Supply Chain Management (GSCM). This research applies the rigorous Analytic Hierarchy Process (AHP) approach and polls industry specialists to evaluate and prioritize the most significant barriers to broad GSCM deployment in the automobile industry. The results show that financial hurdles are the most difficult to overcome, whereas technical and infrastructure hurdles are less than others. This ground-breaking study provides important insights into the barriers to GSCM implementation in Morocco's automotive industry. These results could motivate governments, business leaders, and academics to create concrete plans to address the challenges highlighted here. The primary goal of this study is to promote environmental stewardship and drive corporate growth in Morocco's automotive sector by adopting of green supply chain techniques.JEL Classification: E31, F31, C22How to Cite:Fatih, F. Z., & Zhang, L. (2023). Challenges in Embracing Green Supply Chain in Morocco’s Auto Industry. Etikonomi, 22(2), 473 – 482. https://doi.org/10.15408/etk.v22i1.31300.